Artificial reproduction survey in male European eels Anguilla anguilla (Linnaeus 1758) by paternity assignment - Franchini, Daniele (Alma Mater Studiorum - Università di Bologna, 2022)
The European eel Anguilla anguilla (Linnaeus, 1758) is a critically endangered species whose survival in the wild is largely threatened by human activity. In addition, this vertebrate's unique ecology and biology make it even more vulnerable, and the IUCN listed A. anguilla as severely endangered on the Red List of Threatened Species. In this scenario, captive breeding can represent a significative help for the species' future and many efforts have been dedicated to the artificial reproduction. Ten years ago, dedicated research programs on A. anguilla artificial reproduction started at the DIMEVET (Bologna University). In 2020, based on parentage assignment, some lights were thrown on the reproductive performance in semi-natural conditions. The present study aims to verify if the artificial mixing of male and female gametes would lead to different results in males’ fertilization rates, improving the final rate of genetic variability. We analysed six successful reproduction events. 22 adults and 258 larvae were genotyped by 10 specie-specific microsatellite loci and paternity was allocated to 250 larvae, with a rate of success in parentage assignment of 94%. Even if a locus had to be discarded from the data set for technical reasons, this high rate in allocation success accounts for the good resolution power of the remaining nine loci (mean PIC 0.812). In each reproduction we observed a single male who contributed with 40-70% of the offspring generated, two subordinate males who contributed with 10-30% of the F1 and an “ineffective” one which contributed with 8% or less to F1. This result is homologous to the previous results in semi-natural conditions. The presence of a similar pattern of fertilization rate by different males in both studies, suggest that the behavioural component is unlikely to be the cause of the offspring generation disparity, and other explanations should be considered, like sperm quality and factors that would impact on it.